STUDY ON MATERIAL USED IN KUMAUN FOLK ART - Arya, Sanjeev (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Kumaun region is situated in the eastern of Uttarakhand state. This part of eastern Uttarakhand is known as Kumaun region. Like other provinces, kumauan region if also famous for its folk art. Folk art of this region is named as ‘Aipan’. This folk art is quite similar to ‘Alpana’ and ‘Mandana’ which are famous folk styles from Bengal and Rajasthan. The most important colour used is white which is made by grinding rice into a fine powder, liquefied and then painted using finger tips. Folk life of people of kumaun has a balanced adaptation of dependence and utility with nature. Village life is very much affected by globalization and marketism and in today’s era of synthetic colours, acrylics, print and ceramics, it is necessary to study our experience, inspect it and then make it documented. ‘Aipan’ is mostly painted in kumaun households on the occasion of festivals, auspicious ceremonies and worships. “Since ancient times in Indian folk life, there has been a sense of worship towards the earth and so is the tradition of ‘Aipan’. This tradition of painting aipan on the household walls during major ceremonies, festivals and marriages is age old.” 1 Folk art is the cultural dignity of any nation. “Even in this limitation, the cultures have the same vision in their basic rule. Folk art is of national importance. By consolidating our culture, the land of folk art keeps moving forward at the same pace. There are no convex waves in it, there is no roaring index that is, the respect of the ocean is serious and infinite” 2 . Folk art is generally done using natural and accessible resources. Natural colours are considered pure. Their folk art is filled with emotions of welfare, faith and trust. These folk arts are not the art of any one individual, but the collective art expression of common people. The colours used by cave people during pre-historic times were black, white, red and ochre. Colours were used in limited quantities which is seen in district caves of kumaun such as falsima, petshaal, lakhudiyar,, lwethap, fadaknoli. Colours such as red, ochre, white etc can be seen in these murals. In reference to use of colours in prehistoric times, Dr Premshankar Devidi has quoted: “limited colours were used in the pre-historic times such as gerua, white, khadia, hironji and coal powder. These colours were prepared by grinding using stones. The surface used by these primitive artists were mainly walls and ceilings which were not bounded to a limited dimension.”